Water reuse in Brazilian manufacturing firms - José Féres; Arnaud Reynaud; Alban Thomas (Institute for Applied Economic Research (ipea), 2015)
This paper examines the factors influencing water reuse in manufacturing firms and analyzes whether the structure of intake water demand differs between firms that adopt water reuse practices and those which do not. To this purpose, we estimate a two-stage econometric model based on a sample of 447 industrial facilities located in the Paraíba do Sul river basin. The first stage applies a probit model for the water reuse decision and the second stage employs an endogenous switching regression to estimate the intake water demand equations. Results suggest that water charges may act as an effective mechanism in inducing firms to undertake water reuse investments and reducing intake water demand. Estimates of the water demand price elasticities indicate that plants reusing water are more sensitive to water price increases than plants without access to reuse technologies.
Keywords: Q21; Q25; L5; 330